Crack shape evolution under bending-induced partial closure. (1st February 2018) - Corbani, S.; Castro, J.T.P.; Miranda, A.C.O.; Martha, L.F.; Carter, B.; Ingraffea, A.
Highlights: Shows that shallow corner cracks are not represented by concentric quarter-ellipses. An new fitting by straight lines and non-concentric quarter-ellipses is proposed. Reproduce the evolving geometry of crack front with step-by-step technique. 3D finite element analyses was performed with contact on the crack closure. Abstract: In this paper, crack shape evolution under out-of-plane pure bending loads in plates with an initial through-thickness edge crack is investigated experimentally and computationally. Such cracks were numerically simulated by a step-by-step 3D finite element technique as an attempt to reproduce the evolving geometry of the crack front for the present problem, considering contact on the closed part of the crack faces. The purpose of this numerical analysis was to identify the particular issues of this type of simulation and to demonstrate that it is feasible. In the experiments, beach marks were generated to identify crack front shapes during crack growth. New fitting crack front curves are proposed using straight lines combined with quarter-ellipses with non-concentric centers.